An update on the genetics of alcoholic liver disease - Vishnubhotla, Ravikanth; Kulkarni, Anand V.; Sharma, Mithun; Rao, Padaki Nagaraja; Reddy, Duvvur Nageshwar (Frontiers in Gastroenterology, 2022)
Worldwide, an estimated 2 billion individuals consume alcohol, which contributes to short-term or long-term consequences on health and social life. Alcohol is the cause of approximately 1.8 million deaths per year, representing 3.2% of all deaths worldwide. Of the 2 billion individuals who consume alcohol, more than 75 million are diagnosed with alcohol-use disorder (AUD) and are at an enhanced risk of developing alcoholic liver disease (ALD). However, not all individuals who consume alcohol develop liver disease suggesting the intricate interactions of host genetics with the environment in the precipitation of the phenotype. With advances in genomic technologies, it is now possible to sequence clinically relevant genomic loci associated with a phenotype with precision and faster turnaround times. Genomic data in the form of variants may be used to predict susceptibility to a phenotype in an unaffected individual or may assist the clinician in predicting the outcomes after the onset of the disease. Both of these are crucial as the former would aid in reducing the future burden of the disease, and the latter would help identify and treat individuals at risk of severe liver disease. In the current review, we summarize the pathogenic mechanisms of ALD and discuss the variants identified to date that may aid in predicting alcohol dependence and the development of cirrhosis in individuals with AUD.